Pro database migration to Azure data modernization for the enterprise - Kline, Kevin 1966-; McDowell, Denis; Dorsey, Dustin; Gordon, Matt (Apress L.P., 2022)
Migrate your existing, on-premises applications into the Microsoft Azure cloud platform. This book covers the best practices to plan, implement, and operationalize the migration of a database application from your organization's data center to Microsoft's Azure cloud platform. Data modernization and migration is a technologically complex endeavor that can also be taxing from a leadership and operational standpoint. This book covers not only the technology, but also the most important aspects of organization culture, communication, and politics that so frequently derail such projects. You will learn the most important steps to ensuring a successful migration and see battle-tested wisdom from industry veterans. From executive sponsorship, to executing the migration, to the important steps following migration, you will learn how to effectively conduct future migrations and ensure that your team and your database application delivers on the expected business value of the project. This book is unlike any other currently in the market. It takes you through the most critical business and technical considerations and workflows for moving your data and databases into the cloud, with special attention paid to those who are deploying to the Microsoft Data Platform in Azure, especially SQL Server. Although this book focuses on migrating on-premises SQL Server enterprises to hybrid or fully cloud-based Azure SQL Database and Azure SQL Managed Instances, it also cover topics involving migrating non-SQL Server database platforms such as Oracle, MySQL, and PostgreSQL applications to Microsoft Azure. What You Will Learn Plan a database migration that ensures smooth project progress, optimal performance, low operating cost, and minimal downtime Properly analyze and manage non-technical considerations, such as legal compliance, privacy, and team execution Perform a thorough architectural analysis to select the best Azure services, performance tiers, and cost-containment features Avoid pitfalls and common reasons for failure relating to corporate culture, intra-office politics, and poor communications Secure the proper executive champions who can execute the business planning needed for success Apply proven criteria to determine your future-state architecture and your migration method Execute your migration using a process proven by the authors over years of successful projects Who This Book Is For IT leadership, strategic IT decision makers, project owners and managers, and enterprise and application architects. For anyone looking toward cloud migration projects as the next stage of growth in their careers. Also useful for enterprise DBAs and consultants who might be involved in such projects. Readers should have experience and be competent in designing, coding, implementing, and supporting database applications in an on-premises environment.
Print version record
Keywords: Systems migration; Database management; Microsoft Azure (Computing platform); Migration (Informatique); Bases de données; Gestion; Microsoft Azure (Plateforme informatique)